Traditional Culinary Lexicon In Batak Toba: A Study Of Meaning - Sitinjak, Apriani Silviani; Novia Klopaking Br. Sinaga; Cecylia Damayanti; Han Trexy (Pascasarjana Universitas HKBP Nommensen, 2025)
This study examines the traditional culinary lexicon of the Batak Toba ethnic group in North Sumatra, Indonesia, with a particular focus on the lexical structures and semantic dimensions of traditional food names. Culinary terminology in this community reflects cultural values, indigenous knowledge, and ancestral traditions. The research aims to identify and analyze the morphological processes and semantic interpretations underlying these food names. A qualitative descriptive method was used, employing structured interviews with native Batak Toba speakers, particularly culinary informants, as well as observational techniques. Data were analyzed using lexical semantics and morphological frameworks. Findings reveal that Batak Toba food names are linguistically complex and culturally rich, incorporating elements such as preparation techniques, symbolic meanings, and ritual significance. Terms like arsik, saksang, and naniura convey not only ingredients and methods but also reflect the cosmology and beliefs of the Batak Toba people. This study contributes to the fields of ethnolinguistics, linguistic anthropology, and cultural preservation. It emphasizes the importance of documenting traditional culinary terminology amidst globalization and linguistic homogenization. Future research should broaden the scope to include multiple informants and ethnic subgroups to enhance the generalizability and depth of analysis.